Flowers of Shanghai - Han, Bangqing 1856-1894; Hanno, Yoshihiro 1968- (The Criterion Collection, 2021)
"An intoxicating, time-bending experience bathed in the golden glow of oil lamps and wreathed in an opium haze, this gorgeous period reverie by Hou Hsiao-hsien traces the romantic intrigue, jealousies, and tensions swirling around four late-nineteenth-century Shanghai "flower houses," where courtesans live confined to a gilded cage, ensconced in opulent splendor but forced to work to buy back their freedom. Among the regular clients is the taciturn Master Wang (Tony Leung Chiu-wai), whose relationship with his longtime mistress (Michiko Hada) is roiled by a perceived act of betrayal. Composed in a languorous procession of entrancing long takes, Flowers of Shanghai evokes a vanished world of decadence and cruelty, an insular universe where much of the dramatic action remains tantalizingly offscreen—even as its emotional fallout registers with quiet devastation." [criterion.com]
Original: Taiwan, Japan 1998
Blu-ray special edition features: new 4K digital restoration, with 5.1 surround DTS-HD Master Audio soundtrack ; new introduction by critic Tony Rayns ; "Beautified realism", a new documentary by Daniel Raim and Eugene Suen on the making of the film, featuring behind-the-scenes footage and interviews with Lee, producer and editor Liao Ching-sung, production designer Hwarng Wern-ying, and sound recordist Tu Duu-chih ; excerpts from a 2015 interview with Hou, recorded as part of the Academy of Motion Picture Arts and Sciences’ Oral History Projects ; trailer ; English subtitle translation by Rayns ; plus: An essay by film scholar Jean Ma and a 2009 interview with Hou conducted by scholar Michael Berry
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc